A prospective observational study of prescription appropriateness of elderly hypertensive patients using Beers criteria in a tertiary care teaching hospital - H., Supriya K.; S., Shashi Kumar N.; M., Prakash G.; V., Sareetha A. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The prevalence of hypertension has been increased among the urban population especially among the elderly. Use of inappropriate medication is one of the major problems seen among elderly age group above 60 years who take more medication when compared to that of younger population. Inappropriate prescriptions can be avoided by identifying safer pharmacological alternatives and also utilizing non-pharmacological therapy. Quality and safety of prescribing in elderly patients is one of the global healthcare concern and efforts should be made to improve appropriateness of medication among this group of population. This study was done to assess the relationship between inappropriate medication use and its health outcomes in elderly hypertensive population. Methods: A prospective observational study was conducted over a period of 3 months, after getting approval from Institutional Ethics Committee. Total of 117 elderly hypertensive patients aged >60 years were analysed for three months duration for the rationality of medication prescribed using Beer’s criteria and the health outcome due to inappropriate medication use. Results: Out of 117 elderly hypertensive patients analysed, 49 (41.9%) were males and 68 (58.1%) were females. Most of the patients had associated co morbid illness like diabetes mellitus (48.7%), respiratory diseases (24.8%), cerebrovascular accident (30.8%), cardiovascular diseases (19.7%), fever (13.7%), anaemia (9.4%), etc. Out of 117 patients <5 drugs were used in 6.8%, 5 -10 drugs were used in 89.7% and >10 drugs were used in 3.4% of cases. Antihypertensive drugs that were commonly used in our study was calcium channel blocker (52.1%), diuretics (42.7%), Angiotensin converting enzyme inhibitors (36.8%), β-blockers (17.1%) and Angiotensin receptor blockers (11.1%). Adverse health effects like drug induced gastritis, electrolyte imbalance, metabolic dysfunction and renal impairment was seen in few patients because of inappropriate medication. Conclusions: Use of inappropriate medication is one of the major problems seen among elderly, because of the co morbid illness associated with the primary disease which leads to polypharmacy. Prescription inappropriateness was seen among 86.3% of elderly hypertensive patients as per Beers criteria which may be because of comorbid illness that was seen among these patients. It is necessary to implement certain policies in geriatric healthcare to prevent the poor outcome due to drug therapy.